Studi Integrasi Islam, Sains, dan Budaya Nusantara Perspektif Pendidikan Profetik: Menilik Podcast “Beranda Islami” Fakultas Dakwah UIN Profesor Kiai Haji Saifuddin Zuhri Purwokerto - Fani, Mauliya Nandra Arif; Roqib, Moh. (Jurnal Kependidikan, 2024)
Islam is able to answer all problems following the development of science and technology so that scientific integrations become a necessity. Worship is related to knowing himself, others, nature, and God. To be able to understand all that, one must study knowledge in depth as commanded by Allah Almighty through the Qur'an and the hadith of the Prophet. Meanwhile, prophetic social science is needed which becomes an ijtihad of believers to make the Qur'an a theory of science, expected to be able to solve life's problems. The values contained in it such as humanization, liberation, and transcendence are the main pillars in carrying out scientific integration. Given this, universities as a scientific forum, their presence is important to meet the needs of higher education for their citizens. This can be done by lecturing outside of formal lectures in the classroom. Faculty of Da'wah UIN Prof. K.H. Saifuddin Zuhri (Saizu) Purwokerto uses YouTube as his da'wah study in the form of a podcast entitled "Beranda Islami". Therefore, this paper aims to analyze and describe how the content analysis of the study on the podcast is seen from the integration of general science with Islamic religious science in the context of prophetic education. This research is a qualitative research using a library research approach, so that exploration of the podcast as primary data and reading related articles as secondary data. From this study, it was found that the content of the podcast contains the values of scientific integration that can be understood through the lens of prophetic social values education.